INVESTIGATING THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN TEACHING WRITING NARRATIVE TEXT: A CASE STUDY IN ONE SENIOR HIGH SCHOOL - Karina Febrisa Putri, - (2023)
The purpose of this study is to investigate the implementation of project-based learning in teaching writing narrative text to senior high school students. In order to meet the desired purpose, this study used a qualitative research approach and employed a case study research design. There were twenty-one tenth-grade students in one private senior high school in Bandung, West Java involved in this study. This study collected data from classroom observation that was supported by videotapes and classroom observation checklists. Moreover, this study used the project or the final product as the data as the project is the main topic of project-based learning. Then, these two main data were analyzed using the framework of four phases of project-based learning by Buck Institute of Education (2019) and the seven gold standards of project-based learning by Larmer (2020). Based on the classroom observation, it was discovered that four stages of project-based learning was done in this study, namely launching project, building knowledge, understanding, and skills, developing and critiquing products, and presenting products. In addition, this study also revealed that during the implementation of project-based learning, only six out of seven gold standards of project-based learning by Larmer (2020) were accomplished. These findings occurred because of several problems that were experienced by the students and the teachers during the stages of developing and critiquing product and presenting product, namely miscommunication. Thus, further researchers need to be more prepared for the problems that occur during the implementation of project-based learning.